Haematological Features of White Rats (Rattus norvegicus) Infected with S. pyogenes and Administered with Probiotics (Yogurt) - Novina Rahmawati; Maimun Syukri; Darmawi Darmawi; Indra Zachreini; Utari Zulfiani; Muhammad Yusuf; Rinaldi Idroes (The Scientific World Journal)
This study aimed to study the inhibition activity of lactic acid bacteria probiotics deriving from Acehnese fermented Etawa goat’s milk (yogurt) against Streptococcus pyogenes bacterial infection in rats (Rattus norvegicus). Haematological analysis of the rats’ blood was performed on the following parameters: platelets, leukocytes, lymphocytes, neutrophils, and monocytes, where the data were further processed using ANOVA and Duncan’s test with a confidence level of 95% (0.05). The results revealed that administering yogurt containing probiotics could reduce infections in the throats of rats caused by S. pyogenes. Based on the haematology examination, the probiotic yogurt could maintain the number of platelets, leukocytes, lymphocytes, neutrophils, and monocytes. Statistical significance was obtained when the infected rats were administered with a ±1.00 mL/day dose for seven days of treatment (p<0.05).